INTRODUCTION OF STUDY OF PARTIALLY OR FULLY PROGRAMMABLE SIMULATORS - Gabriela Ifteni; Alina Apostu; Alina Jehac; Cristina Cotea; Nicoleta Ioanid; Oana Tanculescu (Romanian Society of Oral Rehabilitation, 2017)
Partially or fully programmable simulators are designed to reproduce - in part or in full - the anatomical peculiarities of anterior and posterior determinants. In what regards the normal joints and the accurate reproduction of the determinants of occlusion, simulators allow prosthetic restorations that require minimal intraoral adjustments and can be quickly integrated by the stomatognathic system. Next, we shall review the correlations established between the anterior and posterior determinants of mandibular dynamics and occlusal morphology, by referring also to articulator programming. On principle, the more the assessed teeth are closer to one of the determinants, the more the latter influences their morphology. Errors occurring in the shaping of the morphology of prosthetic restorations may range from inessential, by usage of entirely programmable simulators, to major ones, by using partial occluders (small, undersized hinge axis). Assuming a patient's actual intercondylar distance is 90 mm and the used occluder has a 40 mm intercondylar distance, we observe that, on the new restoration, the grooves will be positioned towards the distal (for the maxillary) and towards the mesial (for the mandible).